Bridging the gap: factors influencing the willingness-behavior transformation of older adults in using community care services in urban China - Yang, Liu; Wang, Lijian (Frontiers in Public Health, 2025)
ObjectivesWhile the potential benefits of community care services (CCSs) have been widely recognized, a significant imbalance remains between the high demand for and the low utilization of these services among older adults in China. Therefore, this study aimed to identify key factors influencing the willingness-behavior transformation of older adults to use CCSs, thereby promoting the actual usage and improving their quality of life.MethodsUsing survey data from 1,233 older adults in urban areas across 4 provinces in China, descriptive statistics analysis was conducted to illustrate the basic characteristics of participants, as well as their willingness and willingness-behavior transformation regarding the use of CCSs. Binary logistic regression and multinomial logistic regression models were used to explore the factors influencing both willingness and the willingness-behavior transformation of older adults in using the three CCS categories.ResultsThe willingness of the older adults to use CCSs was high, while the willingness-behavior consistency was relatively low, indicating the great gaps between positive willingness and actual behavior. The willingness of the older adults to use 3 CCS categories was significantly and differently influenced by 13 predisposing factors, enabling factors, and needs factors. Among them, age, sex, marital status, educational level, traditional old-age care belief, neighbor’s attitude, policy advocacy, service affordability, province, health status, and empty nest were identified as the key factors to convert the willingness into behavior.ConclusionThis study highlights key factors to willingness and willingness-behavior transformation for older adults to use CCSs in urban China, and further provides policy implications for government measures to incentivize the older adults’ positive willingness to use CCSs and bridge the gaps between the willingness and the actual behavior.